An Experimental Study to Evaluate Acute Dermal Toxicity of Dhatakyadi Yoga in Wister Rats - Killedar, Ramesh; Emmi, S. V.; Hegde, Harsha (Asian Journal of Pharmaceutical Research and Development, 2014)
Dhatakyadi yoga is a herbal preparation indicated in Agnidagda Vrana (Burns) which reduces daha (burning sensation), sphota (Blisters), vedana (pain) and has Vranaropana(wound healing) action.Prior evaluating its topical effectiveness, the dermal safety has to be established as burn wound is more prone for infection. The present study focuses on establishing the acute dermal safety of Dhatakyadi yoga (Mixture of Woodfordia fruticosa powder and Linseed oil) on wistar rats. To determine the acute dermal toxicity of the Dhatakyadi yoga (DY) in female wister rats. The test substance was applied to depilated area of sighting group animal at the dose of 2000 mg/kg body. Limit test group animals were similarly treated for 14 days. Following dosing, the rats were observed for mortality and clinical signs of toxicity. Body weight was noted weekly. At the end of 14 days observation period all animals were subjected for necropsy and sent for histopathological study. No visible signs of toxicity, such as changes in the respiratory, circulatory, central nervous system, behavioral pattern were observed in the study. Gross pathological examination did not reveal any lesion that could attribute to the toxicity of the substance. Since no mortality was observed in the study, under the condition of this test, it is concluded that dermal LD50 of Dhatakyadi yoga (Herbal wound healing formulation) for Wister rats was ≥2000mg/kg body weight.